Religious Freedom and the Idea of Establishing Islamic State - Hapsin, Abu (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2017)
The idea of Gamwell on“religion as rational” was based on the concept that religious freedom is nothing other than a political discourse that can be figured out only through a democratic resolution. Changing paradigm from “religion as non-rational” to “religion as rational” is a necessary condition for entering a public debate. Yet, the sole public debate or public view is not enough to solve the modern political problematic. The public debate must be guided by a constitutional procedure affirmed by the body politic so that it fulfills the criteria of formal claim about justice. Applying qualitative research and literature review this research tried to reveal: Gamwell’s idea of religious freedom, the features of the Islamic State as described by Abdul Rauf and Gamwell’s concept of religious freedom and the idea of establishing the Islamic State advocated by Abdul Rauf.Gagasan Gamwell tentang